Factors Underlying The Increase in Diabetes Mellitus Patients at The Mopah Health Center, Merauke Regency - Rohmani Rohmani; Ardhanari H Kusuma; Lisda Sinaga (Jurnal Syntax Transformation, 2023)
Background: The International Diabetes Federation (IDF) organization estimates that there are 436 million people aged 20-70 years in the world suffering from diabetes mellitus in 2019 or equivalent to a prevalence rate of 9.3%. Diabetes mellitus (DM) is a metabolic disorder disease caused by reduced insulin production, the body cannot use the insulin produced effectively, or both. Insulin is a hormone produced by pancreatic cells that functions to regulate blood sugar levels. So that there is an increase in the concentration of glucose in the blood which is called hyperglycemia. Research Objectives: To determine the relationship of factors that underlie the increase in diabetes mellitus in the Mopah Health Center Work Area, Mopah Regency. Research Methods: using qualitative research with a cross sectional design. The results of the study: the most female sex amounted to 104 people (64.2%). The most age range between more than 56 years (56.2%). The education of the most respondents is high school, amounting to 102 people (63%). Respondents who have a BMI of more than 25 kg/cm2 are 85 people (52.5%). The most frequent activities were routine activities, amounting to 104 people (64.2). There are factors related to obesity and physical activity that underlie the increase in diabetes mellitus in the working area of the Mopah Health Center. Conclusion: there are no factors of gender, age and education that underlie the increase in people with diabetes mellitus at the Mopah Health Center. There are two factors that underlie the increase in people with diabetes mellitus, namely obesity and physical activity